The Diary of a Bedfordshire Squire : John Thomas Brooks of Flitwick, 1794-1858. (Publications Bedfordshire Hist Rec Soc Ser., 1987)
The Diary of a Bedfordshire Squire: (John Thomas Brooks of Flitwick, 1794-1858) John Thomas Brooks led the life of a country squire, managing his estates, raising a family, serving the county as High Sheriff and on the Ampthill Board of Guardians and socialising with his peer group in the county. These activities are all recorded in his diary together with his particular passion - gardening.